DETERMINING FACTORS OF AGRICULTURAL PRODUCTION IN IRAQ FOR THE PRIOD (1985-2005) - Zouiyed Fatehy Abd (Mesopotamia Journal of Agriculture)
The research aims at studying and analysis the determining factors of agricultural production in Iraq and showing the effect of sharing them in the growth and development of agricultural production for the period (1985-2005) values of agricultural domestic product have been adopted being an affiliated Varian as well as the determining factors and they are : agricultural capital, agricultural work, the farming area, mechanical technology, chemical technology and climatic variables being an independent variables to represent the relation ship among them. It has been confirmed through results of analysis that there is an effect for some independent factors, agricultural work, the farming area and chemical technology in both growth and development of agricultural product ratios of participation in each element have been calculated in the development of the affiliated element .It has been clear that the chemical technology has a larger participation (contribution) amounted 64.7% and the farming area 57.8% ,the capital 31.6% then the agricultural work 14.7% ,climatic variables -14.5% and finally the mechanic technology-54.5%, this shows that the agricultural sector in Iraq suffers from the lack of optimum use of agricultural resources which requires the adoption of an effective agricultural policy through the usage of agricultural plans by using an agricultural policy and modern technology as well as the large financial support given to the farmer and the secured high prices for his products as well as customs protection as long as this sector represents an important location in the national economy.